Private capital flows to Africa : perception and reality - Bhinda, Nils...[et al] (FONDAD The HagueNL, 1999)
Presents the facts on the scale and composition of private capital flows to Africa and the difficulties in monitoring them. Looks at what motivates people to invest and focuses on the macroeconomic impact and policy implications of capital flows. Identifies measures which will help African governments to attract more development-oriented private flows.